Analysis of Rice Milling Machine Maintenance in The Bahagia Village Farmers' Group - Moh Aidil Wahab; Syamsuddin; Asngadi; Suryadi Hadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the implementation of rice milling machine maintenance at the Bina Kasih Farmers Group in Bahagia Village, Palolo District, Sigi Regency. The research method used is a qualitative approach with data collection techniques through in-depth interviews with machine owners and operators and direct observation of the condition and maintenance activities of the rice milling machine. The results show that the Bina Kasih Farmers Group implements two types of machine maintenance: preventive maintenance and corrective maintenance. Preventive maintenance is carried out primarily at the beginning of the harvest season, including machine cleaning, lubrication, and component inspections, while corrective maintenance is carried out after damage occurs, such as replacing filters, drive belts, and husk fans. However, the implementation of maintenance is not supported by a regular and systematic schedule. Lack of attention to machine cleanliness during operation, limited access to spare parts, and a lack of human resources with technical skills are the main obstacles in machine maintenance. These conditions have an impact on machine performance decline, increased repair costs, and potential operational disruptions. Therefore, it is necessary to increase awareness of the importance of regular maintenance, develop a structured maintenance schedule, and strengthen human resource capacity to maintain machine performance and increase farmer group productivity in a sustainable manner.